Human factors and organizational climate of a private higher education institution confessional - Murillo Antón, Walter (2013)
The present work has the goal to explore the organizational climate of a university confessional, through descriptive study, not transecctional experimental. As aresult, this work shows the organizational climate perception of Service’s workers of the denominational private university with an 85, 7%, in contrast to 14.3%, that is found in progress scale. From these data we conclude that there is a good organizational climate it is related to the welfare of workers in the human dimension.